2017
DOI: 10.1002/tia2.20056
|View full text |Cite
|
Sign up to set email alerts
|

Foreign and U.S-Educated Faculty Members' Views on What Constitutes Excellent Teaching: Effects of Gender and Discipline

Abstract: This study identifies views of foreign‐educated faculty who teach in American universities on what constitutes excellence in teaching based on different demographics using the online version of the Teacher Behavior Checklist. Faculty from 14 institutions within the Southern Regional Educational Board (SREB) were asked to rank the top 10 of 28 teacher qualities of excellent teaching. The final faculty sample consisted of 448 participants, of which 309 were U.S.‐educated, and 139 were foreign‐educated. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…Definitions of excellent teaching are remarkably consistent across students (Buskist, Sikorski, Buckley, & Saville, 2002;Faranda & Clarke, 2004;Revell & Wainwright, 2009), faculty (Barnes et al, 2008;Ismail, 2014), administrators (Skelton, 2004), and alumni (Moore & Kuol, 2007;Yair, 2008). Common across these general definitions is the recognition that excellent teaching requires sufficient expertise in content and pedagogy (Bain, 2004;Elton, 1998;Shim & Roth, 2009), although possessing only one or the other is insufficient by itself.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Definitions of excellent teaching are remarkably consistent across students (Buskist, Sikorski, Buckley, & Saville, 2002;Faranda & Clarke, 2004;Revell & Wainwright, 2009), faculty (Barnes et al, 2008;Ismail, 2014), administrators (Skelton, 2004), and alumni (Moore & Kuol, 2007;Yair, 2008). Common across these general definitions is the recognition that excellent teaching requires sufficient expertise in content and pedagogy (Bain, 2004;Elton, 1998;Shim & Roth, 2009), although possessing only one or the other is insufficient by itself.…”
mentioning
confidence: 89%
“…Buskist and colleagues (2002) found that students and faculty agreed that some of the most important aspects of excellent teaching are (a) having realistic expectations and fair grading practices, (b) being knowledgeable about the topic, (c) being approachable and personable, (d) being respectful, (e) being creative and interesting, and (f) being enthusiastic. These qualities generalize across the range of higher education institutions (Ismail, 2014;Schaeffer, Epting, Zinn, & Buskist, 2003;Vulcano, 2007;Wann, 2001). Students from different cultures also tend to value similar aspects of teaching, although there are some differences, for example, students from Eastern cultures prefer more structure to interaction with professors and more certainty about faculty expertise than their Western colleagues (Keeley, Christopher, & Buskist, 2012;Liu, Keeley, & Buskist, 2015).…”
mentioning
confidence: 95%
“…Researchers also examined faculty perceptions of excellent teaching. Ismail and Groccia (2017) found foreign-and US-educated faculty ranked the Top 10 TBC qualities with 80% agreement. With respect to differences, foreign-educated faculty ranked effective communication and caring higher, whereas US-educated faculty valued enthusiasm more.…”
Section: Tbc Findings Across Contextsmentioning
confidence: 96%
“…The TBC is sensitive to the instructional contexts in which it is used, and is useful for studying and understanding excellence in teaching, for example, relative to students' ages (Jõemaa 2013), students' major area of study (Liu et al 2016;Hart and Wang 2016;Noll 2017), location of faculty education (Ismail and Groccia 2017), type of degree sought (Schaeffer et al 2003), academic setting (McConner 2017), cultural context (Keeley, Christopher, and Buskist 2012;Liu et al 2015), and similarities and differences between students and faculty perspectives on what constitutes excellent teaching (Buskist et al 2002). In addition to being a basic research tool to investigate the habits and practices of master teachers, the TBC has been shown to be a useful tool for evaluating teaching at all levels and successfully discriminates among differences in instructional quality.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Each of the scale's items is defined in terms of specific, observable behaviors that teachers might exhibit inside and outside the classroom. The TBC has been used to compare both student and faculty views on college and university teaching with students and faculty showing sizable agreement in the Top 10 qualities and behaviors of master teachers (Buskist et al., ; Ismail and Groccia, ; Schaeffer et al. ).…”
mentioning
confidence: 99%